Post-Modernism and Nepal’s Education - Lamichhane, Shreeram P; Wagley, Mana P (Journal of Education and Research, 2008)
The postmodernist critique of science consists of two interrelated arguments: epistemological and ideological. Both are based on subjectivity. First, because of the subjectivity of the human object, anthropology, according to the epistemological argument, cannot be a science; and in any event the subjectivity of the human subject precludes the possibility of science discovering objective truth. Second, since objectivity is an illusion, science, according to the ideological argument, subverts oppressed groups, females, ethnics, third-world peoples etc. ! e greatest accomplishment of postmodernism is the focus upon uncovering and criticizing the epistemological and ideological motivations in the social sciences. DOI: http://dx.doi.org/10.3126/jer.v1i0.7946 Journal of Education and Research 2008, Vol. 1, No. 1, pp. 9-12